DISKURSUS PAJAK DAN ZAKAT: KONTEKSTUALISASI DAN APLIKASI DI NEGARA MUSLIM - Afriyandi, Yuli (AS-SALAM, 2014)
The problem of tax and tithe (zakat) often make a controvertion in Islamiccountries. This is because Islam in Rasulullah era never charged a tax to theMoslem, and only charge zakat. Beside the obligation of tax is charged tothe non-Moslem people that live in the Islamic era or Islamic authority. Thepractice of collecting tax (jizyah and kharaj) in Nabi SAW era was done bythe collector who had a dualism, that is as a zakat collector and also tax.This policy always continued to the next era. Then in era of Umar bin AbdulAziz made a new reformation and restructured the system of tax.Now, a longing with the development of era, the study of zakat and taxincluding the applicating not only in Islamic countries but also non Islamiccountries makes a controvertion. The thought that apperars is how thecountry must place zakat and tax in order to both have a connection.Indonesia, as a country with the great quantity of Islamic people in theworld has a facilitated the obligation of tax to the Islamic people, withhas releashed the regulation about zakat by the government. But inimplementing there are many obstacles.The truly, tax and zakat are two different terms from source side or basicof their collection, but it is as same as the characteristic as a effort to takeor pick up the wealth form society for social interest. Zakat for interest hasbeen regulated by religion or Allah SWT whereas tax is used to interest thathas regulated by country through valid democration process. The differenceof implementing both becomes problem when in particular side there issimmilarity, that is both has a same way obligatory to pay by society. Tax isforced by stateâs law, but zakat is forced by God.So that in the system of islamic public finance, zakat and tax must be placedas a different acceptance in a principe, but has a same goal. If it is based onnash-nash, it can be concluded that that nash is valid there is two obligationsfor Islamic people (particularly Indonesian Moslem), that is obligation tofufill zakat and tax at once.Keywords: Tax, zakat, public finance.